New Record of Bar-Necked Keelback, Fowlea schnurrenbergeri (Kramer, 1977) (Squamata: Colubridae) in Bangladesh (Bangladesh Journal of Zoology, 2022)
Abstract not availableBangladesh J. Zool. 50 (2): 273-276, 2022